REPRESENTATIVE GOVERNMENT BODIES: LEGITIMACY ISSUES UNDER MARTIAL LAW (Coordinates of Public Administration, 2026)
This article is devoted to clarifying the legitimacy issues of representative government bodies under martial law. It analyzes the specific status of state authorities and local self-government bodies in the context of full-scale aggression by the Russian Federation. It expresses considerations regarding the content and causes of doubts spread in political discourse about the legitimacy of Ukrainian authorities, whose constitutionally defined term of office has expired. The futility of such statements, which are part of the enemy's information and psychological operations and are spread in foreign countries and by certain right-wing radical politicians in Ukraine, is substantiated. It emphasizes that it is fundamentally important under the legal regime of martial law to adhere to the principle of institutional continuity of power, as provided for by the laws of Ukraine. It has been proven that even in the conditions of the War for Ukraine's Independence, the representative authorities are legitimate, as they were elected on the basis of current legislation in accordance with the procedure provided for by law, by a majority of citizens and recognized by society. Objectively caused by the conditions of armed aggression by the russian federation against Ukraine, as defined by the Constitution of Ukraine and the Law of Ukraine «On the Legal Regime of Martial Law», the temporary absence of elections to state authorities and local self-government bodies to a certain extent affects the level of democratic development, violating the established order of formation of representative bodies, but cannot be a basis for doubts about their legitimacy and is a necessary measure, while the current legislation generally creates an adequate basis for the functioning of government institutions